Sensory Preference of Vegan Taco with Young Jackfruit as A Substitute for Beef - Raudhah, Putri Ababil; Putra, Mandradhitya Kusuma; Hidayat, Nova Maulidian (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2024)
Purpose of the study: This study is designed to delve into the intricate realm of sensory preferences related to beef tacos infused with young jackfruit as a viable substitute for traditional beef. By scrutinizing these preferences, the research seeks to illuminate consumer inclinations, offering nuanced insights into the acceptance of alternative meat options, particularly within the context of this widely favored dish. Design/methodology: Employing a comprehensive approach, this research seamlessly integrates qualitative and quantitative methods. The study meticulously evaluates the organoleptic qualities and acceptability of beef tacos infused with jackfruit. Through a nuanced exploration, the research aims to provide a holistic understanding, blending the subjective and objective dimensions, to capture the diverse facets of consumer response to this innovative culinary adaptation. Findings: The study uncovered a favorable sensory preference for beef tacos incorporating young jackfruit, emphasizing its potential as a delectable substitute for traditional beef. Notably, it also highlighted the practical advantage of a shorter cooking time compared to beef, adding a dimension of efficiency to the culinary appeal of using young jackfruit in this context. Research limitations/Implications: This study provides valuable insights into the potential of young jackfruit as a meat substitute in culinary applications, particularly in taco preparation. The findings may be beneficial for researchers, chefs, and those interested in sustainable and plant-based culinary innovations. The study's limitations include a focus on specific taste preferences and the need for broader culinary applications. Novelty/Originality of the study: This research contributes to culinary innovation by showcasing a novel application of young jackfruit as a sustainable and plant-based alternative to beef. The study advances existing knowledge by demonstrating the versatility of jackfruit in recreating the sensory experience of traditional meat-based dishes, offering a promising avenue for those exploring eco-friendly and healthier dietary choices.